Customer Perception Towards Herbal Baby Care Products With Reference To Nagercoil Town (International Journal of Food and Nutritional Sciences, 2022)
Herbal Baby care products play a vital role in the world of babies.Particularly Baby Skin Care Products likeBaby soaps, shampoos, Cleansers and washes are mild and safe for babies. Information about the perceptions of mothers on high-price and good quality baby care products was gathered. The effectiveness of advertisement and sales promotion on creating awareness and increase turnover were also examined. This study, focuses on mothers Perception, it vary from person to person. Different people perceive different thing about the same situation. But more than that, we assign different meaning to what we perceive. Different varieties of the products are available in the market consumers prefer the variety of baby care products for high quality, at reasonable price and attractive wrappers. Most of the consumers are satisfied with quality products and some of the consumers prefer other factors each product differs from one another in terms of price, quality, quantity, offers, advertisement etc., The primary aim of this study is to understand the customer economic factors and awareness level, and factor influencing purchasing of herbal Baby CareProducts. Keywords: Customers, Perception, Baby Care product.